Curious George and the firefighters - Rey, Margret; Rey, H. A. (Hans Augusto), 1898-1977.; Hines, Anna Grossnickle (Boston : Houghton Mifflin, 2004)
While on a field trip to a fire station with Mrs. Gray's class, Curious George goes off on his own and is soon at the scene of a fire, where he finds a way to be helpful.
Accelerated Reader AR
Keywords: Monkeys -- Juvenile fiction; Fire fighters -- Juvenile fiction; Fire departments -- Juvenile fiction; School field trips -- Juvenile fiction; Monkeys -- Fiction; Fire fighters -- Fiction; Fire departments -- Fiction; School field trips -- Fiction